2014
DOI: 10.7314/apjcp.2014.15.12.5063
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Family Caregivers of Cancer Patients Receiving Chemotherapy

Abstract: Background: Cancer is a disease which affects not only patients but also their families physically and emotionally. The purpose of this study was to determine the needs, challenges and ways of coping of caregivers of cancer patients. Materials and Methods: In the study, a phenomenological approach was used. Data were collected through semi-structured individual interviews. The study sample comprised 16 family members providing care for a cancer patient. Results: The study findings are grouped under four main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 28 publications
3
48
1
1
Order By: Relevance
“…In Turkey, the family plays an important role in patient care. It is a tradition and considered an obligation to take care of a family member who is sick at home as well as during medical care (Hacioğlu et al, 2010;Sercekus et al, 2014). Firstly, this study revealed that QoL scores were lower among female than among male caregivers.…”
Section: Discussionmentioning
confidence: 66%
“…In Turkey, the family plays an important role in patient care. It is a tradition and considered an obligation to take care of a family member who is sick at home as well as during medical care (Hacioğlu et al, 2010;Sercekus et al, 2014). Firstly, this study revealed that QoL scores were lower among female than among male caregivers.…”
Section: Discussionmentioning
confidence: 66%
“…Darunee Jongudomkarn 1 *, Colin Macduff 2 and organizations (Kostak et al, 2014;Sercekus et al, 2014;Taylor et al, 2013;Yaakup et al, 2014). Accordingly it is important to learn from initiatives taken forward in this field.…”
Section: Development Of a Family Nursing Model For Prevention Of Cancmentioning
confidence: 99%
“…In addition, cancer is an important cause of illness and mortality in Thailand and around the world (Duangsong et al, 2013;WHO, 2010). Prevention, caring, and recovery efforts depend on various family-and community-based interventions, theories and for these to be successful a participatory approach is necessary (Ahmadian and Samah, 2013;Al-Azri et al, 2014;Danawala et al, 2014;Erbil and Bolukbas, 2014;Jo et al, 2014;Lin et al, 2014;Sano et al, 2014;Sercekus et al, 2014;Simayi et al, 2013). However, realizing nursing and health caring that emphasizes family as a key focus of care within the family and community context can be a significant challenge for healthcare educators, practitioners RESEARCH ARTICLE…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that cancer is a disease that affects not only patients but also their families emotionally. Sercekus et al 27 found that family members hide their feelings for fear that it might sadden the patient, avoiding talking about the disease and experiencing difficulty in coping with the patient's reactions such as anger, irritability, etc, arising during the treatment process. Family members need support more than usually appreciated by health care providers.…”
Section: Discussionmentioning
confidence: 99%